If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -20 = 6x + -40 Reorder the terms: -20 + 5x = 6x + -40 Reorder the terms: -20 + 5x = -40 + 6x Solving -20 + 5x = -40 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -20 + 5x + -6x = -40 + 6x + -6x Combine like terms: 5x + -6x = -1x -20 + -1x = -40 + 6x + -6x Combine like terms: 6x + -6x = 0 -20 + -1x = -40 + 0 -20 + -1x = -40 Add '20' to each side of the equation. -20 + 20 + -1x = -40 + 20 Combine like terms: -20 + 20 = 0 0 + -1x = -40 + 20 -1x = -40 + 20 Combine like terms: -40 + 20 = -20 -1x = -20 Divide each side by '-1'. x = 20 Simplifying x = 20
| 0.5x+y=-2 | | z^2-(5+2i)z+21+i=0 | | 3x-3=4y-y | | 2+10y-15=3 | | 0.13y+0.09(y+7000)=1510 | | y=0.5+9 | | 12m+2n-6m+9n= | | z^2-(5+2i)+z+21+i=0 | | -13x+7y=-21 | | g(x)=x^2+6x-16 | | 12x-88=4(-2x-7) | | 4x+21=29 | | 3s/5=21 | | 3(25x+80)=-2(15x-15) | | 2(x+10)=2x+10 | | 2[1.65]+13.86+6.93=12.54 | | 4x-4=-4(-x+1) | | (1.3g+3)(4g+5)= | | -5+14x=7(2x)-5 | | (3n+5)(4n+5)= | | -6x+1=-3(2x+1)+x | | 6y+11=43 | | X^2-15x+12=-6+4 | | 5x-3(x-1)-39= | | (2+3c)(4+6c+9c)= | | (2a-1)(a+3a+5)= | | 435*13= | | X+3=-3-5 | | 46.1*46.1=18.5*18.5+2(11.17)x | | 2(3x-5)=-(x-11) | | 2s-2=2 | | (a+2a-9)(a+3)= |